Flow Visualization in Materials Processing Practical Techniques and Selected Applications - Uemura, Tomomasa (Mathematics for Industry,, 2018)
This book presents a comprehensive review of particle image velocimetry (PIV) and particle tracking velocimetry (PTV) as tools for experimental fluid dynamics (EFD). It shares practical techniques for high-speed photography to accurately analyze multi-phase flows; in particular, it addresses the practical know-how involved in high-speed photography, including e.g. the proper setup for lights and illumination; optical systems to remove perspective distortion; and the density of tracer particles and their fluorescence in the context of PIV and PTV. In this regard, using the correct photographic technique plays a key role in the accurate analysis of the respective flow. Practical applications include bubble and liquid flow dynamics in materials processes agitated by gas injection at high temperatures, mixing phenomena due to jet-induced rotary sloshing, and wettability effects on the efficiency of the processes. .